Solve for m 3(m-2)-5=8-2(m-4)

3(m-2)-5=8-2(m-4)
Simplify 3(m-2)-5.
Simplify each term.
Apply the distributive property.
3m+3⋅-2-5=8-2(m-4)
Multiply 3 by -2.
3m-6-5=8-2(m-4)
3m-6-5=8-2(m-4)
Subtract 5 from -6.
3m-11=8-2(m-4)
3m-11=8-2(m-4)
Simplify 8-2(m-4).
Simplify each term.
Apply the distributive property.
3m-11=8-2m-2⋅-4
Multiply -2 by -4.
3m-11=8-2m+8
3m-11=8-2m+8
3m-11=-2m+16
3m-11=-2m+16
Move all terms containing m to the left side of the equation.
Add 2m to both sides of the equation.
3m-11+2m=16
5m-11=16
5m-11=16
Move all terms not containing m to the right side of the equation.
Add 11 to both sides of the equation.
5m=16+11
5m=27
5m=27
Divide each term by 5 and simplify.
Divide each term in 5m=27 by 5.
5m5=275
Cancel the common factor of 5.
Cancel the common factor.
5m5=275
Divide m by 1.
m=275
m=275
m=275
The result can be shown in multiple forms.
Exact Form:
m=275
Decimal Form:
m=5.4
Mixed Number Form:
m=525
Solve for m 3(m-2)-5=8-2(m-4)

Our Professionals

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top